Aqueous phase synthesis of 2-D copper nanosheets stabilized by organic moieties with enhanced photocatalytic and biological activity. - Sohail, Asma; Fatriasari, Widya; Zia, Sobia; Shahnaz; Irshad , Shagufta (Acta Chimica Asiana, 2024)
Copper nanosheets supported by organic ligands are significant for biological, electrical, and catalytic applications. The discovery that the coronavirus has a significantly reduced maximum survival period on copper surfaces has elevated the utility of copper nanomaterials. Here, we report a non-hazardous and inexpensive biological technique for forming copper nanosheets (Cu Nsts); synthesis of Cu Nsts has always been a challenge for researchers due to the significant problem of oxidation; in this research, we have successfully synthesized stable Cu Nsts by using Saussurea lappa root extract for the first time, the obtained Cu Nsts has a shiny black color with self-standing ability, the crystal structure of Cu nanosheets was determined using Powder X-ray diffraction (PXRD), Scanning electron microscopy (SEM) revealed that copper nanoparticles grow and aggregates to form Cu Nsts. The surface morphology of Cu Nsts is clear evidence of their synthesis. These nanosheets were very proficient in the deduction of harmful dye (methylene blue); within 105 minutes, the degradation capacity of Cu nanosheets for methylene blue reached 93.493%. This remarkable property of Cu Nsts as a photocatalyst gives potential application for removing dyes from industrial wastewater. Cu Nsts showed excellent antioxidant and antibacterial activity. The Cu Nsts demonstrated potent inhibitory zones against E. coli, with inhibition zones measuring 39 mm. This research lays the foundations for purifying wastewater from harmful dyes and bacteria.